Tribological improvement of thermal-sprayed Ti-based coatings modified by 1200 K nitridation - Somchai Thongtem (2018)
Hardness and wear resistance of thermal-sprayed coatings of titanium containing 0, 3, 5 and 10 wt% bond coat (Ni5Al5Mo) were improved by 1200 K nitridation in 5, 10 and 15 ml.s-1 ammonia for 5 h. The improvement was due to the formation of TiN and Ti2N and governed by the ammonia flow rates and the percentage of bond coat. In addition, the coatings were analysed using a scanning electron microscope to determine the distribution of phases and cavities. © 2005 Trans Tech Publications, Switzerland.